Nitrogen fertilization coupled with iron foliar application improves the photosynthetic characteristics, photosynthetic nitrogen use efficiency, and the related enzymes of maize crops under different planting patterns - Nasar, Jamal; Wang, Gui-Yang; Ahmad, Shakeel; Muhammad, Ihsan; Zeeshan, Muhammad; Gitari, Harun; Adnan, Muhammad; Fahad, Shah; Khalid, Muhammad Hayder Bin; Zhou, Xun-Bo; Abdelsalam, Nader R.; Ahmed, Gamal A.; et al. (Frontiers in Plant Science, 2022)
Photosynthetic rate (Pn) and photosynthetic nitrogen use efficiency (PNUE) are the two important factors affecting the photosynthesis and nutrient utilization of plant leaves. However, the effect of N fertilization combined with foliar application of Fe on the Pn and PNUE of the maize crop under different planting patterns (i.e., mono-cropping and intercropping) is elusive. Therefore, this experiment was conducted to determine the effect of N fertilization combined with foliar application of Fe on the photosynthetic characteristics, PNUE, and the associated enzymes of the maize crop under different planting patterns. The results of this study showed that under intercropping, maize treated with N fertilizer combined with foliar application of Fe had not only significantly (p < 0.05) improved physio-agronomic indices, but also higher chlorophyll content, better photosynthetic characteristics, and related leaf traits. In addition, the same crop under such treatments had increased photosynthetic enzyme activity (i.e., rubisco activity) and nitrogen metabolism enzymes activities such as nitrate reductase (NR activity), nitrite reductase (NiR activity), and glutamate synthase (GOGAT activity). Consequently, intercropping enhanced the PNUE and soluble sugar content of the maize crop, thus increasing its yield compared with mono-cropping. Thus, these findings suggest that intercropping under optimal N fertilizer application combined with Fe foliation can improve the chlorophyll content and photosynthetic characteristics of maize crops by regulating the associated enzymatic activities. Consequently, this results in enhanced PNUE, which eventually leads to better growth and higher yield in the intercropping system. Thus, practicing intercropping under optimal nutrient management (i.e., N and Fe) could be crucial for the better growth and yield, and efficient nitrogen use efficiency of maize crop.